Anatomical factors influencing traditional abdominal examination in Kampo diagnosis: Analysis by computed tomography. Issue 1 (1st December 2020) - Shimada, Hirobumi; Namiki, Takao; Hirasaki, Yoshiro; Oji, Takeshi; Nakaguchi, Toshiya; Ueda, Keigo; Kasahara, Yuji; Nagamine, Koichi; Okamoto, Hideki; Yakubo, Shuji
ABSTRACT: Aim: In Japanese‐Oriental (Kampo) medicine, the abdominal examination is an important diagnostic method. We examined the influence of anatomical factors in Kampo medicine on the Kampo diagnosis of abdominal aortic pulsation using abdominal computed tomography (CT). Methods: Our subjects were 67 patients (34 men, 33 women; average age: 61.4 ± 16.3 years) who underwent abdominal CT in the Department of Japanese‐Oriental 'Kampo' Medicine at Chiba University Hospital. We measured the depth of the abdominal artery from the midline of the body surface and the blood vessel diameter at that point, and calculated the averages of these parameters among all patients at three locations of abdominal aortic pulsation (epigastrium, supra‐umbilical region, and infra‐umbilical region) on the CT section. Results: The detection rate of abdominal aortic pulsation was highest in the supra‐umbilical region (30%), followed by the epigastrium (21%) and the infra‐umbilical region (15%). The average depth of the aorta from the body surface was shallowest in the supra‐umbilical region (74.9 mm) and deepest at the epigastrium (103.5 mm). As the depth of the artery decreased at the epigastrium and supra‐umbilical region, significant abdominal aortic pulsation was observed ( P = 0.006 and P = 0.001, respectively). Conclusion: Our study demonstrates that abdominal aortic pulsation is anatomically associated with the depth of the artery. The supra‐umbilical region appeared to be the most suitable location for evaluating abdominal aortic pulsation, as the aortic artery is shallowest at that point and is least influenced by the depth of the abdominal artery.